Probing Immune-Mediated Clearance of Acute Middle Ear Infection in Mice - Dewan, Kalyan K.; Sedney, Colleen; Caulfield, Amanda D.; Su, Yang; Ma, Longhuan; Blas-Machado, Uriel; Harvill, Eric T. (Frontiers in Cellular and Infection Microbiology, 2022)
Acute Otitis Media (AOM) is commonly caused by bacterial pathobionts of the nasopharynx that ascend the Eustachian tube to cause disease in the middle ears. To model and study the various complexities of AOM, common human oto-pathogens are injected directly into the middle ear bullae of rodents, or are delivered with viral co-infections which contribute to access to the middle ears in complex and partially understood ways. Here we present the novel observation that Bordetella bronchiseptica, a well-characterized respiratory commensal/pathogen of mice, also efficiently ascends their Eustachian tubes to colonize their middle ears, providing a flexible mouse model to study naturally occurring AOM. Mice lacking T- and/or B-cells failed to resolve infections, highlighting the co-operative role of both in clearing middle ear infection. Adoptively transferred antibodies provided complete protection to the lungs but only partially protected the middle ears, highlighting differences between respiratory and oto-immunology. We present this as a novel experimental system that can capitalize on the strengths of the mouse model to dissect the molecular mechanisms involved in the generation and function of immunity within the middle ear.